Circulating metabolites and lipids are associated with glycaemic measures in South Asians. Issue 2 (25th December 2020) - Gadgil, Meghana D.; Kanaya, Alka M.; Sands, Caroline; Lewis, Matthew R.; Kandula, Namratha R.; Herrington, David M.
ABSTRACT: Background: South Asians are at higher risk for diabetes (DM) than many other racial/ethnic groups. Circulating metabolites are measurable products of metabolic processes that may explain the aetiology of elevated risk. We characterized metabolites associated with prevalent DM and glycaemic measures in South Asians. Methods: We included 717 participants from the Mediators of Atherosclerosis in South Asians Living in America (MASALA) study, aged 40–84 years. We used baseline fasting serum for metabolomics and demographic, behavioural, glycaemic data from baseline and at 5 years. We performed LC‐MS untargeted metabolomic and lipidomic analysis with targeted integration of known signals. Individual linear and ordinal logistic regression models were adjusted for age, sex, BMI, diet, exercise, alcohol, smoking and family history of DM followed by elastic net regression to identify metabolites most associated with the outcome. Results: There were 258 metabolites with detectable signal in >98% of samples. Thirty‐four metabolites were associated with prevalent DM in an elastic net model. Predominant metabolites associated with DM were sphingomyelins, proline (OR 15.86; 95% CI 4.72, 53.31) and betaine (OR 0.03; 0.004, 0.14). Baseline tri‐ and di‐acylglycerols [DG (18:0/16:0) (18.36; 11.79, 24.92)] were positively associated with fasting glucose and long‐chain acylcarnitines [CAR 26:1 (−0.40; −0.54, −0.27)] were inversely associated with prevalent DM and HbA1c at follow‐up. Discussion: A metabolomic signature in South Asians may help determine the unique aetiology of diabetes in this high‐risk ethnic group. Future work will externally validate our findings and determine the effects of modifiable risk factors for DM.